Network Diffusion-Based Prioritization of Autism Risk Genes Identifies Significantly Connected Gene Modules - Mosca, Ettore; Bersanelli, Matteo; Gnocchi, Matteo; Moscatelli, Marco; Castellani, Gastone; Milanesi, Luciano; Mezzelani, Alessandra (Frontiers in Genetics, 2017)
Autism spectrum disorder (ASD) is marked by a strong genetic heterogeneity, which is underlined by the low overlap between ASD risk gene lists proposed in different studies. In this context, known molecular interactions can be used to screen several genome-wide analyses in order to underline those network regions harboring genetic variations associated with ASD, the so-called “disease modules”. In this work, we used a recent network-diffusion based approach to jointly analyze multiple ASD risk gene lists. We defined genome-scale prioritizations of human genes in relation to ASD genes from multiple studies, found significantly connected gene modules associated with ASD and predicted genes functionally related to ASD risk genes. Most of them play a role in synapsis and neuronal development and function; many are related to syndromes that can be in comorbidity with ASD and the remaining are involved in epigenetics, cell cycle, cell adhesion and cancer.